Residue analysis of smoking pipe fragments from the Feltus archaeological site, Southeastern North America. (February 2018) - Carmody, Stephen B.; Kassabaum, Megan C.; Hunt, Ryan K.; Prodanovich, Natalie; Elliott, Hope; Russ, Jon
Abstract: The practice of pipe smoking was commonplace among indigenous cultures of the Eastern Woodlands of North America. However, many questions remain concerning what materials were smoked and when tobacco first became a part of this smoking tradition. Chemical analysis of organic residues extracted from archaeological smoking pipes is an encouraging avenue of research into answering questions regarding the development of a smoking complex within indigenous cultures of the Eastern Woodlands. In the right environmental conditions, absorbed organic compounds within artifacts can remain structurally stable for millennia, allowing analyses of organic matter to be performed on relics of advanced age. In this study, organic matter from six pipe fragments derived from the prehistoric Feltus site in Mississippi was extracted and analyzed via GC-MS, a process that allows for the identification of compounds in a complex mixture. Preliminary experiments tested the effects of pH on the efficacy of our extraction solvent to maximize the detectability of alkaloids such as nicotine. Several notable compounds were identified, including nicotine, which serves as a biomarker for tobacco. Highlights: GC-MS results of smoking pipe residue analysis Alternative way to identify tobacco use at prehistoric archaeological sites in North America Ritual plant use